MHC class IIB exon 2 polymorphism in the Grey partridge (Perdix perdix) is shaped by selection, recombination and gene conversion. - Marta Promerová (Public Library of Science (PLoS), 2013)
Among bird species, the most studied major histocompatibility complex (MHC) is the chicken MHC. Although the number of studies on MHC in free-ranging species is increasing, the knowledge on MHC variation in species closely related to chicken is required to understand the peculiarities of bird MHC evolution. Here we describe the variation of MHC class IIB (MHCIIB) exon 2 in a population of the Grey partridge (Perdix perdix), a species of high conservation concern throughout Europe and an emerging galliform model in studies of sexual selection. We found 12 alleles in 108 individuals, but in comparison to other birds surprisingly many sites show signatures of historical positive selection. Individuals displayed between two to four alleles both on genomic and complementary DNA, suggesting the presence of two functional MHCIIB loci. Recombination and gene conversion appear to be involved in generating MHCIIB diversity in the Grey partridge; two recombination breakpoints and several gene conversion events were detected. In phylogenetic analysis of galliform MHCIIB, the Grey partridge alleles do not cluster together, but are scattered through the tree instead. Thus, our results indicate that the Grey partridge MHCIIB is comparable to most other galliforms in terms of copy number and population polymorphism.